Upconverting nanoparticle clustering based rapid quantitative detection of tetrahydrocannabinol (THC) on lateral-flow immunoassay. Issue 2 (11th November 2020) - Chand, Rohit; Mittal, Neha; Srinivasan, Seshasai; Rajabzadeh, Amin Reza
Abstract : Cannabis, also known as marijuana, is the most abused psychoactive drug worldwide. Abstract : Cannabis, also known as marijuana, is the most abused psychoactive drug worldwide. Several countries are legalizing the medicinal and recreational use of cannabis. At the same time, stricter laws are being drafted for driving or working under the influence of the drug. Therefore, there is a significant need for rapid point-of-care testing of cannabis in biological fluids. Tetrahydrocannabinol (THC) is the parent psychoactive molecule present in cannabis and is used as a biomarker for cannabis detection. In this work, we developed an upconverting nanoparticle (UCNP) based lateral-flow immunoassay (LFIA) for the point-of-care quantitative detection of THC in oral fluids of drug-impaired personnel. UCNPs convert near-infrared excitation into visible emissions and have superior properties over other fluorescent nanoparticles. We employed a novel signal amplification technique for enhancing the sensitivity of LFIA. Contrary to standard LFIA biosensors, we integrated an additional enhancement pad (EP) between the conjugate pad (CP) and nitrocellulose membrane. UCNPs dually conjugated with THC specific immunoglobulin G and streptavidin (UCNP–IgG–SA) and UCNPs conjugated with biotin (UCNP–biotin) were dried in CP and EP, respectively. UCNP–IgG–SA, upon interacting with THC, flow through the EP and bind with UCNP–biotin, consequently forming bright UCNP clusters on the test and control zones. The test signals were captured after an assay time of 20 minutes. An experimental detection limit of 2 ng mL −1 for THC with a linear detection range of 2–15 ng mL −1 was achieved. The developed LFIA has the potential to be used as a point-of-care detection device for the quantitative detection of THC.